Zinc Oxide Nanowires Synthesized Using A Hot Tube Thermal Evaporation Under Intermediate Heating Period - Samsudi Sakrani; Peshawa Omer Amin; Syahida Suhaimi (Penerbit UTM Press, 2024)
ani et al. / Malaysian Journal of Fundamental and Applied Sciences Vol. 9, No.4 (2013) 20